Alpha-1-antitrypsin-deficiency is associated with lower cardiovascular risk: an approach based on federated learning - Zöller, Daniela; Haverkamp, Lars Christian Arndt Simon; Makoudjou, Adeline; Sofack, Ghislain; Kiefer, Saskia; Gebele, Denis; Pfaffenlehner, Michelle; Boeker, Martin; Binder, Harald; Karki, Kapil; Seidemann, Christian; Schmeck, Bernd; et al. (Respiratory research, 2024)
Chronic obstructive pulmonary disease (COPD) is an inflammatory multisystemic disease caused by environmental exposures and/or genetic factors. Inherited alpha-1-antitrypsin deficiency (AATD) is one of the best recognized genetic factors increasing the risk for an early onset COPD with emphysema. The aim of this study was to gain a better understanding of the associations between comorbidities and specific biomarkers in COPD patients with and without AATD to enable future investigations aimed, for example, at identifying risk factors or improving care.